Prevent postpartum blues with the implementation of breastfeeding father education model to increase the frequency of breastfeeding in mothers: A systematic review - Gusti Ayu Martha Winingsih; Ummu Salmah; Masni; Rahayu Indriasari; Ridwan Amiruddin; Agus Bintara Birawida (Elsevier, 2021)
Objective: To find out if the breastfeeding father education model can increase exclusive breastfeeding in mothers to prevent the occurrence of postpartum blues. Methods: This study uses literature review design, articles collected using search engines such as PubMed, Elsevier, Scinapse, Plos One, and Google Scholar. We identified journals based on the PRISMA 2015 Guidelines with a total of n = 5690 and obtained the number of journals reviewed n = 33. Results: The father's support is believed to have influenced the mother's decision to start and maintain breastfeeding. Father education is proven to increase breastfeeding with a value of p (0.001) < 0.05. In addition, support from husbands is also classified as sufficient (54%) in lowering anxiety levels in mothers with spearman's test results p = 0.48 or <0.05. Conclusions: Providing an education model of breastfeeding father can increase the exclusive breastfeeding by the mother to prevent the occurrence of postpartum blues.